Determination of North Sulawesi Agricultural Insurance Premiums Based on Rainfall Index Using the Black-Scholes Model - Novianti, Saqila; Nugraha, Dwita Safira; Wiliya, Wiliya (Operations Research: International Conference Series, 2021)
This article discusses the use of the Black Scholes model to calculate insurance premium prices based on the rainfall index. The Black Scholes model is one of the models used to determine option prices. The research method used is to study the material through mathematics journals and collect data. The data used in this study are rainfall data and rice production data in North Sulawesi from 2018 to 2020. Based on the results and discussion, the quarterly rainfall data that has a strong correlation is the third quarter rainfall. At the 5th percentile, the third quarter rainfall data is 450.22 mm. For the latest rainfall data size (450.22 mm) the premium obtained is IDR 231,912.09. From the calculation results, the higher the value for both sizes, the greater.